(untitled) (International Association of Biologicals and Computational Digest, 2024)
In India, out of195 species of Euphorbia sub-genus, about 23 species have been recorded in the state of Gujarat, out of which phytochemical work has been done on only 12–13 species. These Euphorbia species have ethnobotanical significance and are used by indigenous communities. The research work on these species has till now displayed the presence of phytochemicals and secondary metabolites like phenolic compounds, flavonoids, tannins, terpenes, terpenoids, cardiac glycosides, etc., which are used in the treatment of skin disorders, arthritis, cancer treatment, cytotoxicity, etc. The purification of the phytochemicals revealed the exact chemical structure of the compounds present, which may help in further research and overlap with fields such as phylogenetics, cell biology, molecular biology, enzymology, etc. There is future scope for research in the investigation of phytochemicals of Euphorbia sp., like E. rosea Retz., E. orbiculate H. B. & K, on which research work has not been conducted yet.